2013
DOI: 10.1016/j.bbr.2013.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Chronic electromyographic analysis of circadian locomotor activity in crayfish

Abstract: Animals generally exhibit circadian rhythms of locomotor activity. They initiate locomotor behavior not only reflexively in response to external stimuli but also spontaneously in the absence of any specific stimulus. The neuronal mechanisms underlying circadian locomotor activity can, therefore, be based on the rhythmic changes in either reflexive efficacy or endogenous activity. In crayfish Procambarus clarkii, it can be determined by analyzing electromyographic (EMG) patterns of walking legs whether the walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Given the relatively quiescent nature of the animals prior to actual ecdysis, the fairly immediate onset of ecdysis after mechanical stimulation may act as a form of defense, where the rhythmic motions may act as deterrents to predation. This is not surprising since many walking central pattern generators show both rhythmic and reflexive (to mechanical stimulation; Tomina et al, 2013) responses. Mechanical stimulation has been shown to induce premature eclosion in moths, even with no apparent adaptive value (Kammer and Kinnamon, 1977).…”
Section: Discussionmentioning
confidence: 95%
“…Given the relatively quiescent nature of the animals prior to actual ecdysis, the fairly immediate onset of ecdysis after mechanical stimulation may act as a form of defense, where the rhythmic motions may act as deterrents to predation. This is not surprising since many walking central pattern generators show both rhythmic and reflexive (to mechanical stimulation; Tomina et al, 2013) responses. Mechanical stimulation has been shown to induce premature eclosion in moths, even with no apparent adaptive value (Kammer and Kinnamon, 1977).…”
Section: Discussionmentioning
confidence: 95%
“…Muscle activity has been used as an indicator of behavioral onset in previous studies (Kagaya and Takahata, 2010;Kagaya and Takahata, 2011). Electromyographic studies (Chikamoto et al, 2008;Tomina et al, 2013) revealed that the temporal pattern of leg muscle (merocarpodite flexor) activation is statistically different between spontaneously evoked and stimulus-evoked walking. In the current study, we made EMG recordings from the crusher claw muscles of lobster to characterize the motor program subserving spontaneous initiation of the grasping action by cheliped for manipulating foodstuff.…”
Section: Discussionmentioning
confidence: 99%
“…In the EMG studies using human subjects, it has been shown that EMG activity patterns are different in voluntary and stimulation-evoked muscle contraction (Hoffer et al, 1996). Previous studies using crayfish also successfully characterized EMG patterns in spontaneously initiated walking as different from those in mechanical stimulus-evoked walking (Chikamoto et al, 2008;Tomina et al, 2013). Those investigations revealed that a specific muscle of the walking leg was tonically activated prior to the onset of rhythmical stepping movements or bursting activity when the animal initiated walking spontaneously, and this pre-activation time was relatively shorter in the reflexive walking (Chikamoto et al, 2008;Tomina et al, 2013).…”
Section: Muscle Activity Patterns In Spontaneous Grasping Behaviormentioning
confidence: 99%
See 2 more Smart Citations